The ITS-rDNA region as a complementary or alternative phylogenetic marker to 18S-rDNA in rumen ciliates (Alveolata, Ciliophora) - Silva, Zacarias Rosalina João Da; Cedrola, Franciane; Senra, Marcus Vinicius Xavier; Rossi, Mariana Fonseca; Dias, Roberto Júnio Pedroso (Zootaxa, 2025)
Rumen ciliates are important constituents of gastrointestinal microbiome of herbivorous mammals. They are traditionally classified based on morphological characteristics. However, molecular markers—mainly the 18S rRNA gene—have increasingly been used to investigate their evolutionary relationships. While the 18S gene provides reliable phylogenetic resolution at higher taxonomic levels, it lacks variability to distinguish closely related taxa. In this study, we evaluated the potential of the internal transcribed spacer (ITS) rDNA region as an alternative or complementary marker to the 18S rRNA gene for phylogenetic reconstruction of rumen ciliates. We generated and analyzed ITS sequences from rumen ciliate species and compared topologies obtained using three datasets: ITS alone, 18S alone, and a concatenated ITS+18S dataset. The concatenated dataset consistently showed improved resolution and support across several key clades, supporting its utility in Trichostomatia phylogeny. Some differences were observed, such as the variable placement of Troglodytella abrassarti, highlighting the importance of multi-marker approaches. Our findings demonstrate that the ITS region is a robust complementary marker that enhances phylogenetic resolution, especially when combined with 18S data.